Experimental study on tin slag polymer concrete strengthening under compression with metallic material conﬁnement - Muhamad Soffi, Manda; Mohd Ruzaimi, Mat Rejab; Shukur, Abu Hassan; Mat Uzir, Wahit; Nurhadiyanto, Didik (MDPI, 2023)
Studies on the external strengthening of tin slag polymer concrete by fibre-reinforced plastic confinement have provided strength enhancement of tin slag polymer concrete up to 128% with carbon fibre-reinforced plastic confinement. However, the effect of metallic material confinement has yet to be studied. This article presents the experimental finding on tin slag polymer concrete strengthening through metallic material confinement under compressive loads. Machined mild steel metal tube has been employed to strengthen tin slag polymer concrete core in partial and fully confinement prior to compression testing. Through this study, compressive strength of tin slag polymer concrete short column has been enhanced with the metal tube confinement application from 59.19 MPa (unconfined) to 95.86 MPa (partial metal confinement) and 131.84 (full metal confinement) representing 61.95% and 122.74% of strength enhancement percentage. Material behaviour analysis through stress versus strain curves has revealed that the strain softening curve is modified by metal tube confinement before a fracture occurs on both partial and full metal confinement samples compared to the control sample (unconfined). In addition, the failure modes have indicated that the high ductility of metallic confinement material has effectively confined tin slag polymer concrete from sudden fracture where the metal tube in partial confinement indicates ductile expansion while the metal tube in full confinement has shown ductile crushing. In general, it was concluded that metallic material confinement on tin slag polymer concrete under compressive load has resulted in providing strength enhancement and modified the failure mode of tin slag polymer concrete. Finally, further research is recommended, especially by initiating numerical analysis to facilitate parametric studies on tin slag polymer concrete for structural material design.